Pigmented Mammary Paget Disease with Reticulated Features: A Rare Variant of Mammary Paget Disease - Lee, Eun Ah (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
Pigmented mammary Paget disease (PMPD) is a rare subtype of mammary Paget disease that presents as a hyperpigmented patch or plaque over the areola and nipple. We herein report on an unusual case of PMPD with reticulated features in a 98-year-old female. The histology showed intraepidermal pagetoid cells containing melanin pigments without any underlying intraductal carcinoma.